The Erotics of History An Atlantic African Example - Donham, Donald (University of California Press, 2018)
The Erotics of History challenges long-standing notions of sexuality as stable and context-free-as something that individuals discover about themselves. Rather, Donald L. Donham argues that historical circumstance, local social pressure, and the cultural construction of much beyond sex condition the erotic. Donham makes this argument in relation to the centuries-old conversation on the fetish, applied to a highly unusual neighborhood in Atlantic Africa. There, local men, soon to be married to local women, are involved in long-term sexual relationships with European men. On the African side, these couplings are motivated by the pleasures of cosmopolitan connection and foreign commodities. On the other side, Europeans tend to fetishize Africans' race, while a few search to become slaves in master/ slave relationships. At its most wide ranging, The Erotics of History attempts to show that it is history, both personal and collective, in reversals and reenactments, that finally produces sexual excitement.